Analysis of Revenue Allocation of Power Plants - Bangviwat, Athikom; Chaisinboon, Orathai; Puapattanakul, Apinya (European Journal of Applied Sciences, 2025)
The study focuses on the returns to factors of electricity production by six (6) different technologies, which are natural gas-fired, coal-fired, biomass, hydropower, wind turbine, and solar photovoltaic power plants. Cash flow analysis is used to identify the allocation of the plants' revenues to the owners of the factors of production and stakeholders through the companies' financial statements to different factors of production, namely fuels, operation and maintenance expense, utilities, personnel wages, taxes, interests, loans, and dividends, in addition to the investment promoting parameters, like payback period, net present value, and internal rate of return, to fulfill the requirement for sustainable development. Power plants of different technologies, require different proportions of factors of production, and investments. The revenues are allocated to the owners of the factors of the production, including fuel and utility suppliers, workers, owners, financial institutes, as interests and loans, and the government and society as taxes. The major expenses of natural gas-fired, coal-fired, and biomass power plants are for operation activities, including fuel costs and O&M costs. Differently, for other technologies, which are hydropower, wind turbine, and solar photovoltaic power plants, the major portions of their revenue are re-turned to the investing activities of the power plants.